Konsep Pendidikan Spiritual - UJUD SUPRIAJI (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2019)
In the context of educating the nation's life, spiritual intelligence is very important play a role in the world of education because in fact in this life not only only intellectual intelligence is needed that is logical, realistic but also it takes a spirit to have godliness, that is truly aware of life we have someone who controls, regulates and determines, namely Allah SWT, so do we must realize very well that every achievement, and a great achievement because his will, so that humans are only able to try and beg, pray to Allah SWT, which in this case is the Implementation of Spiritual Education in every individual who lives in this world , so that every achievement is a great achievement must be accompanied by the extent of the person's business and spiritual level. Study this aims to describe the process of spiritual education, describe whether the implementation of quetiont spiritual education in mts padureso can improve madrasah achievements, and describe the problems that arise and what the solutions are. From the results of the study there are several conclusions including: that there is a difference a very significant condition between before spiritual education and after the implementation of spiritual education quetiont in the presence of valid evidence what the researchers found was a change in attitude, namely after routine educationSpiritually both teachers and students become more calm in heart, honest attitude, discipline, increasing day by day. Although there are problems inhibiting implementation Implementation of Spiritual Education quote, especially at the beginning of implementation, namely students are still difficult to regulate and so that order has not been realized properly, but over time with a solution to the application of rules accompanied by teacher supervision that is intense so that after a while the child emerges self-awareness without coercion from anywhere to carry out spiritual education quetiont.